Using choice experiments to understand visitors preferences for the man-made lake ecotourism services in Terengganu, Malaysia - Wan Muhamad, Wan Nur Hidayah; Radam, Alias; Yacob, Mohd Rusli (International Institute for Science, Technology and Education, 2014)
This paper aims to capture the level of satisfaction of the visitors towards the ecotourism service attributes at Kenyir Lake, by providing results of a valuation study on the boat house services, which is the main focus in this research. A choice experiment is employed to estimate the visitors’ preferences for boat house service attributes. The attributes investigated were visitors guide (TG), provision of safety equipment (SAFE), coverage for communication system (COMM), package of activities (ACTV) and extra package price (EPP). The simple conditional logit (CL) model and CL interaction model were estimated in order to identify the preferences of the visitors from various service options of boat house attributes. This study presents implications for the policy makers in guiding the future management and the improvement of boat house services. The results of this study will be able to facilitate the future management in establishing an efficient implementation in order to improve the boat house services to fulfill the visitors’ satisfaction.